Pengaruh Social Media Marketing dan Sales Promotion Terhadap Keputusan Pembelian Tastea Perintis Kemerdekaan Makassar - Tamara, Kirana Lorenza The; Jaya, Amir; Halik, Johannes Baptista (Al-Buhuts, 2023)
This research aims to see the influence of marketing using social media and sales promotions on consumer purchasing decisions at the Tastea Perintis Independen Makassar branch. The population in this study were all Tastea customers at the Perintis Independen Makassar branch, where the author took a sample of 50 people based on convenience sampling techniques. From the research results, it was found that Social media marketing (X1) had no effect on Tastea consumer purchasing decisions (Y). On the other hand, sales promotion (X2) has a positive and significant influence on consumer purchasing decisions (Y). For this reason, the author suggests that Tastea look for other digital marketing tools that are considered appropriate for reaching their consumers. Apart from that, they continue to strengthen sales promotions which are their advantage.